SISTEM PENJUALAN TOKO “JANGKAR PRUSIK” BERBASIS WEB - Ardianingtyas, Ade; Purwatiningtyas, Purwatiningtyas (Information Technology and Telematics, 2018)
Abstraction The development of information technology and communication science is now quite rapidly growing with the internet. This also affects the development of the economy in Indonesia. Economic development in Indonesia also affect the lifestyle of people in doing transactions that initially met directly, now a transaction through online media, one of which is the website. One businessman who sees opportunities from the utilization of this website is a store called "Jangkar Prusik" which sells accessories such as necklaces and bracelets. Therefore, researchers want to create a system of selling "Jangkar Prusik" Web-based store to facilitate the sale of this store. The making of this website uses Waterfall method from Roger S. Pressman (2001) which initially started with system requirement analysis, system design, implementation, program testing, and maintenance. This website is made to facilitate the management of existing data. In addition, also to facilitate the marketing, promotion, and product sales online at the "Jangkar Prusik" store. From the results of system testing performed, the system is able to facilitate the management of existing data. In addition, the system can also facilitate the marketing, promotion, and sale of products at the "Jangkar Prusik" store. The system is also capable of providing monthly transaction reports containing the date of purchase, consumer name, the name of the purchased product, the amount of product purchased, the unit price, shipping costs, and the total payment.